Defining the optimal duration for normothermic regional perfusion in the kidney donor: A porcine preclinical study. Issue 3 (17th September 2018) - Kerforne, Thomas; Allain, Geraldine; Giraud, Sebastien; Bon, Delphine; Ameteau, Virginie; Couturier, Pierre; Hebrard, William; Danion, Jerome; Goujon, Jean‐Michel; Thuillier, Raphael; Hauet, Thierry; Barrou, Benoit; et al.
Abstract : Kidneys from donation after circulatory death (DCD) are highly sensitive to ischemia‐reperfusion injury and thus require careful reconditioning, such as normothermic regional perfusion (NRP). However, the optimal NRP protocol remains to be characterized. NRP was modeled in a DCD porcine model (30 minutes of cardiac arrest) for 2, 4, or 6 hours compared to a control group (No‐NRP); kidneys were machine‐preserved and allotransplanted. NRP appeared to permit recovery from warm ischemia, possibly due to an increased expression of HIF1α‐dependent survival pathway. At 2 hours, blood levels of ischemic injury biomarkers increased: creatinine, lactate/pyruvate ratio, LDH, AST, NGAL, KIM‐1, CD40 ligand, and soluble‐tissue‐factor. All these markers then decreased with time; however, AST, NGAL, and KIM‐1 increased again at 6 hours. Hemoglobin and platelets decreased at 6 hours, after which the procedure became difficult to maintain. Regarding inflammation, active tissue‐factor, cleaved PAR‐2 and MCP‐1 increased by 4‐6 hours, but not TNF‐α and iNOS. Compared to No‐NRP, NRP kidneys showed lower resistance during hypothermic machine perfusion (HMP), likely associated with pe‐NRP eNOS activation. Kidneys transplanted after 4 and 6 hours of NRP showed better function and outcome, compared to No‐NRP. In conclusion, our results confirm the mechanistic benefits of NRP and highlight 4 hours as its optimal duration, after which injury markers appear. Abstract : The authors report a preclinical porcine model for normothermic regional perfusion in the kidney donor used to specify the mechanisms involved and to optimize the duration of the procedure.